(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2025)
Floating marine debris (FMD) is created mostly as a result of anthropogenic activities and represents a global threat to marine environments and organisms. The origin and abundance (density and distribution) of FMD greatly vary both spatially and temporally. Hence, it is required to assess the presence of FMD globally, regionally, and locally to enable effective control. Assessment of FMD accumulation in the intertidal zones provides significant insight into the status of marine pollution. However, surveys of FMD on the beaches physically require huge manpower, time, money and intensive efforts. An autonomous unmanned aerial vehicle (UAV) could facilitate assessing and monitoring the FMD of a wide range of areas at a low cost with minimum time and effort. In this study, for the first time in Bangladesh, we identified the FMD in the intertidal zones through geospatial tools and techniques using high-resolution UAV images by conducting a survey on Manpura Island from 1st to 3rd December 2022, located in the central Meghna Estuary. The flight was operated at a height of 40 meters above the ground, allowing for the acquisition of images with a resolution of 1.2 cm. Images were collected from eight different locations covering all four sides of the island for spatial comparison; 400-600m2 area for each of the locations. Segment Mean Shift Algorithm (SMSA) was used to identify the debris. A total of 412 debris items were identified, and the density and distribution of FMD were then presented on a map. The method and results of this study will act as a baseline for policymakers in developing countries for sustainable monitoring and management of FMD. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 14(1), 2025, P 101-111